1992
DOI: 10.1002/chir.530040512
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the enantiomers of drugs containing amino alcohol structure after derivatization with bromoacetic acid

Abstract: The separation of the enantiomers of drugs containing an amino alcohol structure like adrenergic drugs or 0-blockers is described. The compounds are resolved on chiral ligand-exchange chromatography phases after derivatization with bromoacetic acid. 0 1992 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Moreover, it is the key functionality in beta‐blockers and adrenergic drugs. For many beta‐blockers, the pharmacological activity is attributed to the S‐ enantiomers and for adrenergic drugs it is the R‐ enantiomers . Recently, Mullie et al .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, it is the key functionality in beta‐blockers and adrenergic drugs. For many beta‐blockers, the pharmacological activity is attributed to the S‐ enantiomers and for adrenergic drugs it is the R‐ enantiomers . Recently, Mullie et al .…”
Section: Introductionmentioning
confidence: 88%
“…For many beta-blockers, the pharmacological activity is attributed to the S-enantiomers and for adrenergic drugs it is the R-enantiomers. [6] Recently, Mullie et al reported that the enantiomeric pairs of 4-amino alcohol quinoline derivatives showed difference in the malarial activity, i.e. S-enantiomer showed 2-15 folds better activity than its counter form (Renantiomer).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the cardioselectivity and β‐blocking activity of S ‐enantiomers of aryloxypropanol amine is 50–500 times more than the R ‐enantiomers. Several strategies for the synthesis of acebutolol have been reported in the literature (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…Several strategies for the synthesis of acebutolol have been reported in the literature (Scheme 1). [22][23][24][25] Only a few reports are available for the enantiopure synthesis of this drug molecule. One of the reported strategies (strategy 1) uses chiral halohydrin or glyceryl acetonide to convert phenol 3 to enantiopure halohydrin 5.…”
mentioning
confidence: 99%
“…Several authors report on the indirect separation of amino alcohol enantiomers by ligand-exchange HPLC (LE-HPLC) using different derivatization reagents [1][2][3]. Direct separation of amino alcohol enantiomers by LE-HPLC often causes problems, since the pH optimum for complexation for amino alcohols is at high pH.…”
Section: Introductionmentioning
confidence: 99%